THE IMPACT OF PADLET-BASED INTERACTIVE STRATEGY ON STUDENTS' SPEAKING SKILLS AT SENIOR HIGH SCHOOL - Rizka Maulidya; Jamilah Jamilah (Universitas Darussalam Gontor, 2026)
This study was conducted to address the need for more engaging and effective approaches to improving senior high school students’ speaking skills. Traditional teaching methods often provide limited opportunities for meaningful oral interaction; therefore, integrating ICT-based interactive strategies is expected to create more student-centered and communicative learning environments. The purpose of this study was to investigate the effect of ICT-based interactive strategies, particularly Padlet, on students’ speaking performance. A quasi-experimental design was employed involving an experimental group and a control group. The experimental group received instruction through ICT-based interactive strategies using Padlet as the primary digital platform, whereas the control group was taught using conventional methods. Data were collected through speaking performance tests administered as pre-tests and post-tests and analyzed using parametric statistical procedures. The findings indicated significant improvement in students’ speaking skills over time, with F(3,76) = 74.758, p = .000 (p < .05), and a very large effect size (η² = .747). Both the experimental group (40.25 to 78.00) and the control group (41.25 to 76.25) demonstrated considerable improvement; however, no statistically significant difference was found between the groups’ post-test scores. These findings suggest that Padlet-mediated instruction contributes to speaking development by fostering interactive, collaborative, and multimodal communication opportunities, although its effectiveness was comparable to that of conventional instruction. Therefore, ICT-based interactive strategies may serve as a valuable complementary approach within an integrated English language teaching framework rather than as a replacement for conventional methods.